Study the Characterization of Adding Polymer-Surfactant Agent on the Drag Reduction Phenomena in Pipeline Flow System - Dawood, Sahar A. (Al-Khwarizmi Engineering Journal, 2017)
Abstract    In this study, the effect of carboxylic methyl cellulose (CMC), and sodium dodcyl benzene sulfonate (SDBS) as an aqueous solution on the drag reduction was investigated. Different concentrations of (CMC) and (SDBS) such as (50, 100, 150, 200, 250, 300, 350, 400, 450, and 500 ppm) were used to analyze the aqueous solution properties, including surface tension, conductivity, and shear viscosity. The optimum four concentrations (i.e., 50, 100, 200, and 300 ppm) of fluid properties were utilized to find their effect on the drag reduction. Two different PVC pipe diameters (i.e., 1" and 3/4") were used in this work. The  results showed that blending CMC with SDBS gives a good drag reduction percent about (58%) more than using them individually, friction factor decreasing with increasing Reynolds number and gives good agreement with von Karamn equation and maximum drag reduction (MDR) asymptote. Reynolds number, pipe diameter, and polymer-surfactant concentrations were considered as influencing factors. In addition, critical micelle concentration, the onset of drag reduction, and the interactions between the mixed additives were discussed. Keyword: CMC, SDBS, drag reduction, friction factor, blending of additives.